Strengthening Technology, Performance And Competitivness Of Apple Carang Mas “Arum Sari” In Batu City - Siti Asmaul Mustaniroh (Journal of Innovation and Applied Technology, 2015)
ABSTRACT Batu City is wellknown as apple icon as apple and aplle based products producer. " Small Medium Enterprses (SMEs) "Arum Sari" has developed innovative apple carang mas which has high demand and grows market, but this SME can not fill the market share. The main problems faced by SMEs is the improvement of production building and outlet for diplaying "Arum Sari" products with hygienic standards. Partially implementation of GMP for food production, as well as the limitations of technology transfer for production of carang mas, impact on quality and production quantity. Based on these reaosons, the strengthening of technology to improve efficiency and productivity of the Arum Sari is required. The results of this activity include a technology transfer and renovation of production and display rooms.  Mechanical shredder machine and spinner, have been used for carang mas production. Socialization of GMP, SOP and quality control in the production process have been carried out to the workers and owners of SMEs "Arum Sari" so that the product is more higyine and safe for consumption. Keywords: apple, carang mas, performance production, stengthening